226k views
2 votes
2/3 (m + 4) = 1/5 (3m+9)

2 Answers

4 votes

Answer:

m = - 13

Explanation:

2/3 (m + 4) = 1/5 (3m+9)

2/3m + 8/3 = 3/5m + 9/5

2/3m - 3/5m = 9/5 - 8/3

10/15m - 9/15m = 27/15 - 40/15

1/15m = - 13/15

m = - 13/15 / 1/15

m = - 13/15 * 15

m = - 195/15

m = - 13

User Shakena
by
5.3k points
5 votes


(2)/(3) (m+4) = (1)/(5) (3m+9)


(2m+8)/(3) = (3m+9)/(5)

10m + 40 = 9m + 27

10m - 9m = 27 - 40

m = -13

User Markus Jevring
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.